Composition effects on the fcc-hcp martensitic transformation and on the magnetic ordering of the fcc structure in Fe-Mn-Cr alloys - Guerrero Salazar, Lina Maria (2017)
This paper presents an experimental study on the fcc/hcp martensitic transformation temperatures (MTTs) and Néel temperatures (TN) of the fcc phase of Fe-Mn-Cr alloys. A wide range of chemical compositions (13.7 < Mn < 27.5 wt.% and 0 < Cr < 12.4 wt.%) has been studied. X-ray diffraction measurements were conducted in order to confirm that the martensitic transformation takes place between an fcc structure and the hcp martensite. Transition temperatures were measured by means of electrical resistivity and dilatometry. All transition temperatures tend to decrease with the increment in Cr content while the addition of Mn decreases the MTTs and increases TN. These different effects and the stabilization effect of the antiferromagnetic ordering on the fcc austenite result in different MTTs behaviors depending on whether the martensitic transition occurs from a magnetically ordered austenite or not. For these later cases, a phenomenological model of MTTs is presented that could be of use for alloys design.